GOVERNANCE, FISCAL DECENTRALIZATION, AND GROWTH IN INDONESIA - Digdowiseiso, Kumba (Jurnal Sosial dan Humaniora, 2016)
This study tries to disentangle whether governance and fiscal decentralization in Indonesia improves economic growth in 1984 â 2014. Also, it investigates whether there is causality in governance-fiscal decentralization-growth in Indonesia. The results run by OLS (Ordinary Least Square) and VECM (Vector Error Correction Model) method provide different intrepretation, however one could argue that VECM can best describe the relationship between growth and governance as well fiscal decentralization both in short and long run since simple OLS are usefull when all variables are stationary at levelÂ Keywords : Governance, Fiscal, Decentralization, Growth, Indonesia